Unlocking value co-creation in entrepreneurial ecosystems: The vital role of institutions - Yuko Inada (Administrative Sciences, 2024)
The entrepreneurial ecosystem is quite complicated because of the presence of numerous stakeholders and the inclusion of multicultural and social elements in diverse communities. The role of entrepreneurship education in developing entrepreneurial skills and aptitude has evolved. The collaboration between universities, companies, and organizations in the collaborative online international learning (COIL) approach plays an important role in the entrepreneurial ecosystem to enhance value co-creation. To extend the limited literature on value creation through entrepreneurship education among stakeholders and analyze the entrepreneurial ecosystem from a micro perspective, this study investigated why companies and organizations support universities at the individual, organizational, and institutional levels to foster entrepreneurial ecosystems. Following a global career course using the COIL approach, semi-structured interviews were conducted in person or via Zoom with four representatives of the Embassy of Canada to Japan, Ernst & Young, and Manulife from April to May 2022. The modified grounded theory approach was used to analyze the responses from three institutions. The results showed that students were provided with the opportunity to solve actual issues that the three institutions faced and the students' perspectives were considered to identify and develop high-quality proposals at the individual, organizational, and institutional levels. The institutional philosophy, organizational engagement and development, and personal development of the representatives of these institutions effectively create values within universities while also forming entrepreneurial ecosystems at Japanese and Canadian companies, organizations, and universities to help build the next generation of leaders. This study has important implications through its contribution to society and the development of an entrepreneurial ecosystem in collaboration with the academic, industrial, and public sectors.
Keywords: 350; entrepreneurial ecosystem; entrepreneurship education; value co-creation; collaborationonline international learning (COIL); higher education